Testosterone modulates structural synaptic plasticity of primary cultured hippocampal neurons through ERK - CREB signalling pathways. (1st March 2020) - Guo, Guoxin; Kang, Lin; Geng, Dandan; Han, Shuo; Li, Sha; Du, Juan; Wang, Chang; Cui, Huixian
Abstract: Although hippocampus-derived androgens play an important role in hippocampal synaptic plasticity, studies at the cellular level have received relatively less attention. Furthermore, the underlying signalling pathways associated with synaptic plasticity remain unclear. Results of the present study demonstrated that testosterone treatment of primary cultured rat hippocampal neurons resulted in a rapid increase in spine density, accompanied by the elevation of protein and messenger RNA levels of synaptophysin, developmentally regulated brain protein (Drebrin), and the N-methyl-D-aspartate receptor NR1 subunit. Testosterone treatment also increased the phosphorylation levels of extracellular-regulated protein kinase (ERK)1/2 and cAMP-responsive element binding protein (CREB), rather than p38 and Jun N-terminal kinase (JNK). U0126 significantly reversed the testosterone-mediated phosphorylation of CREB. Importantly, the increase in spine density was not induced by testosterone under U0126 treatment. These findings suggest that the ERK1/2-CREB signalling pathway plays an important role in testosterone-mediated rapid spinogenesis of cultured rat hippocampal neurons. Results of this study will be helpful in further clarifying the physiological function of testosterone and related signalling pathways in vitro. Highlights: Testosterone upregulated rapidly spinogenesis of primary cultured hippocampal neurons. T-mediated spinogenesis of cultured hippocampal neurons work through ERK1/2-CREB signalling pathway. Local synthese of special synaptic proteins (SYN, Drebrin and NR1) were involved in the T-modulated spinogenesis.